2018
DOI: 10.32800/amz.2018.16.0163
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal parasites in a population of stone marten (Martes foina) in central Spain

Abstract: Intestinal parasites in a population of stone marten (Martes foina) in central Spain. Twentyone fresh fecal samples from stone marten (Martes foina) (Erxleben, 1777) collected in the Natural Park of Hoces del Río Riaza (Segovia) were processed using a modified version of Ritchie's concentration method. We identified 18 genera: four coccidian; two trematodes; three cestodes; eight nematodes; and one acanthocephalan. The prevalence was low for all genera except Isospora sp. (Schneider, 1875), Eimeria sp. (Schnei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…In fact, Nájera et al [35] reported, for the same population in study, a case of interspecific killing and partial consumption of a feral cat by an Iberian lynx individual, which evidence the disease risk and possible outbreak that this domestic/feral species can represent for the Iberian lynx, especially in small/newly reintroduced populations. With the exception of T. cati, which is more cat-specific, according to Ribas et al [36] and Olmedo et al [37], most of the parasites found in this study have low host specificity and have mutual wild carnivores' families, which can be explained by their similar generalist diet composition. Rodríguez and Carbonell [14] also found low prevalence and diversity of parasites among the mesocarnivores analysed, especially in the stone marten, the genet, and the Egyptian mongoose.…”
Section: Discussionsupporting
confidence: 48%
“…In fact, Nájera et al [35] reported, for the same population in study, a case of interspecific killing and partial consumption of a feral cat by an Iberian lynx individual, which evidence the disease risk and possible outbreak that this domestic/feral species can represent for the Iberian lynx, especially in small/newly reintroduced populations. With the exception of T. cati, which is more cat-specific, according to Ribas et al [36] and Olmedo et al [37], most of the parasites found in this study have low host specificity and have mutual wild carnivores' families, which can be explained by their similar generalist diet composition. Rodríguez and Carbonell [14] also found low prevalence and diversity of parasites among the mesocarnivores analysed, especially in the stone marten, the genet, and the Egyptian mongoose.…”
Section: Discussionsupporting
confidence: 48%
“…Three host species, the Asian palm civet ( Paradoxus hermaphroditus ) ( Sepelage and Rajakaruna 2020 ), spotted hyena ( Crocuta Crocuta ) ( Engh et al , . 2003 ) and stone marten (also known as beech marten) ( Martes foina ) ( Olmedo et al, 2018 ; Figueiredo et al, 2018 ) have been described as harbouring Toxocara spp. eggs whereas the Egyptian mongoose ( Herpestes ichneumon ) ( Radwan et al, 2009 ) and the American mink ( Neovision vison) ( Tull et al, 2022 ) were described as harbouring T .…”
Section: Other Non-canid or Non-felid Hostsmentioning
confidence: 99%